2017
DOI: 10.1161/jaha.117.005801
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Use of Oral Anticoagulants for Atrial Fibrillation: A Report From the National Cardiovascular Data Registry (NCDR ® ) PINNACLE Registry

Abstract: BackgroundDespite higher thromboembolism risk, women with atrial fibrillation have lower oral anticoagulation (OAC) use compared to men. The influence of the CHA 2 DS 2‐VASc score or the introduction of non–vitamin K OACs on this relationship is not known.Methods and ResultsUsing the PINNACLE National Cardiovascular Data Registry from 2008 to 2014, we compared the association of sex with OAC use (warfarin or non–vitamin K OACs) overall and by CHA 2 DS 2‐VASc score and examined temporal trends in OAC use by sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 54 publications
5
90
1
6
Order By: Relevance
“…This may be related to a slightly higher rate of increasing prescription of apixaban over time among women than men. A prior U.S. study using registry data in 2010–2014 also found that NOAC use increased at a slightly higher rate in women relative to men . According to a meta‐analysis, compared with men, women treated with a NOAC had a lower risk of major bleeding while those treated with warfarin had a higher risk of stroke and systemic embolism, suggesting an increased net clinical benefit of NOACs compared with warfarin in preventing stroke among women with AF …”
Section: Discussionmentioning
confidence: 95%
“…This may be related to a slightly higher rate of increasing prescription of apixaban over time among women than men. A prior U.S. study using registry data in 2010–2014 also found that NOAC use increased at a slightly higher rate in women relative to men . According to a meta‐analysis, compared with men, women treated with a NOAC had a lower risk of major bleeding while those treated with warfarin had a higher risk of stroke and systemic embolism, suggesting an increased net clinical benefit of NOACs compared with warfarin in preventing stroke among women with AF …”
Section: Discussionmentioning
confidence: 95%
“…Our findings of a lower risk of severe bleeding in women compared to men should be viewed in the light of the risk benefit balance for stroke prevention in women with AF on warfarin, where the differences in the epidemiology of stroke among women and men must be acknowledged. In Sweden, men are more frequently prescribed antithrombotic treatment compared to women [44], and the national US registry data show that women were significantly less likely to use any oral anticoagulant for AF overall and at all levels of CHA 2 DS 2 -VASc score compared to men [45]. Data from a global register study on patients with newly diagnosed NVAF show that the use of anticoagulant therapy for stroke prevention is similar for women and men (approximately 60%), with underuse of anticoagulation therapy in high-risk patients reported for both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…The South Korean CODE-AF registry showed no significant difference in the prescription of anticoagulation between women and men, though women prescribed DOACs were more likely to be insufficiently dosed [ 29 ]. The PINNACLE National Cardiovascular Data Registry from 2008-2014 showed women were less likely to receive oral anticoagulation at all CHA 2 DS 2 -VASc scores, by a factor of up to 33% [ 65 ].…”
Section: Management: Stroke Risk Reductionmentioning
confidence: 99%